Effect of laboratory‐isolated Lactobacillus plantarum LGFCP4 from gastrointestinal tract of guinea fowl on growth performance, carcass traits, intestinal histomorphometry and gastrointestinal microflora population in broiler chicken. Issue 5 (7th January 2017) - Vineetha, P. G.; Tomar, S.; Saxena, V. K.; Kapgate, M.; Suvarna, A.; Adil, K.
Summary: The study aimed to investigate the effect of feed supplements, viz Lactobacillus plantarum LGFCP4 (laboratory isolate from GIT of Guinea fowl), Lactobacillus acidophilus (NCDC, Karnal) and in‐feed antibiotic bacitracin methylene disalicylate (BMD) on growth performance, FCR, carcass traits and immune organs weight, intestinal histomorphometry and gastrointestinal microflora population in broiler chickens. In a completely randomized design, CARIBRO‐Dhanraja broiler chicks ( n = 160) were used with four treatment groups. During the entire experimental duration of 35 days, treatment groups were provided with different dietary treatments (T1 – basal diet (negative control), T2 – antibiotic growth promoter BMD 20 g/100 kg feed (positive control), T3 – 1 × 10 8 cfu of L. acidophilus /gm‐fermented feed +MOS 1 g/kg feed and T4 – 1 × 10 8 cfu of laboratory‐isolated L. plantarum LGFCP4/gm‐fermented feed+ MOS 1 g/kg feed. After 35 days of experimental period, no significant results have been observed in different growth performance traits among treatment groups. Cut‐up parts and edible organs' weight remained unaffected by dietary supplementation, whereas weight of immune organs were significantly higher (p < 0.05) in L. plantarum LGFCP4‐supplemented group. At the end of feeding trial, significantly (p < 0.05) lower E. coli count was observed in crop of T4 birds, while in ileum, T2 and T3 showed lower count. In caeca, T2 group showed lowest E. coli count. Salmonella count in crop and ileum was significantly (p < 0.05) low in T3 and T4, while in caeca, T2 group showed lowest count. In terms of histomorphometry, duodenal villous height (VH), crypt depth (CD) and VH:CD ratio were higher for T3 and T4 and lowest values were obtained for T2 group. The results of the study showed that L. plantarum LGFCP4 isolated from GIT of guinea fowl can effectively replace in‐feed antibiotic growth promoters in broiler diets by altering intestinal villi morphology and improving the gut health by reducing the pathogenic microbial load.